2022
DOI: 10.3390/v14061346
|View full text |Cite
|
Sign up to set email alerts
|

Association of Increased Programmed Death Ligand 1 Expression and Regulatory T Cells Infiltration with Higher Hepatocellular Carcinoma Recurrence in Patients with Hepatitis B Virus Pre-S2 Mutant after Curative Surgical Resection

Abstract: Although surgical resection is available as a potentially curative therapy for hepatocellular carcinoma (HCC), high recurrence of HCC after surgery remains a serious obstacle for long-term patient survival. Therefore, the discovery of valuable prognostic biomarkers for HCC recurrence is urgently needed. Pre-S2 mutant is a mutant form of hepatitis B virus (HBV) large surface protein which is expressed from the HBV surface gene harboring deletion mutations spanning the pre-S2 gene segment. Pre-S2 mutant-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…25,26 Moreover, the presence of pre-S2 gene deletion mutation in combination with high levels of PD-L1 expression and Treg infiltration have been correlated with a higher risk of HCC recurrence after curative surgical resection than either one or two of these three biomarkers. 27 However, to date, the relationship between pre-S2 gene deletion mutation and cytokine expression levels in HBV-related HCC patients remains largely unknown. Therefore, to identify the cytokines with altered expression levels in HBV-related HCC patients with pre-S2 gene deletion mutation would be promising for not only providing new insights into pre-S2 mutant regulation of tumor immune microenvironment (mediation through upregulation of cancer-promoting cytokines or downregulation of cancer-inhibiting cytokines) but also discovering potential biomarkers to be combined with pre-S2 gene deletion mutation for better prediction of poor patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Moreover, the presence of pre-S2 gene deletion mutation in combination with high levels of PD-L1 expression and Treg infiltration have been correlated with a higher risk of HCC recurrence after curative surgical resection than either one or two of these three biomarkers. 27 However, to date, the relationship between pre-S2 gene deletion mutation and cytokine expression levels in HBV-related HCC patients remains largely unknown. Therefore, to identify the cytokines with altered expression levels in HBV-related HCC patients with pre-S2 gene deletion mutation would be promising for not only providing new insights into pre-S2 mutant regulation of tumor immune microenvironment (mediation through upregulation of cancer-promoting cytokines or downregulation of cancer-inhibiting cytokines) but also discovering potential biomarkers to be combined with pre-S2 gene deletion mutation for better prediction of poor patient prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that HCC patients with pre‐S2 gene deletion mutation have significantly higher expression of the immune checkpoint molecule programmed death ligand 1 (PD‐L1) and higher infiltration of the anti‐inflammatory lymphocyte regulatory T cells (Tregs) in tumor tissues than patients without pre‐S2 gene deletion mutation, suggesting the association of pre‐S2 gene deletion mutation with dysregulated tumor immune microenvironment in HBV‐related HCC 25,26 . Moreover, the presence of pre‐S2 gene deletion mutation in combination with high levels of PD‐L1 expression and Treg infiltration have been correlated with a higher risk of HCC recurrence after curative surgical resection than either one or two of these three biomarkers 27 . However, to date, the relationship between pre‐S2 gene deletion mutation and cytokine expression levels in HBV‐related HCC patients remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…As the cervical microbiota are important factors for disease progression, this study suggests further studies to ascertain the role of other viruses as cofactors in carcinogenesis and/or markers of disease progression. Jeng et al report that deletion mutations in the HBV surface protein pre-S2, increased levels of PD-L1 expression, and regulatory T (Treg) cell infiltration into the tumor tissues may help to predict a high risk for recurrence of hepatocellular carcinoma (HCC) [ 2 ]. Next, Koubek et al provide promising results showing that natural compounds in the schweinfurthin family can be used as chemotherapeutic agents to treat Merkel cell carcinoma (MCC) [ 3 ].…”
mentioning
confidence: 99%